Development of a Laparoscopic Surgical Training System with Simulation Open Framework Architecture (SOFA) - Kim, Youngjun; Kim, Kyunghwan; Roy, Frederick; Park, Sehyung (COMPUTER AIDED SURGERY, 2011)
With a number of advantages over traditional laparotomy, laparoscopic surgery is a successful minimally invasive surgical procedure. However, laparoscopy demands high surgical skill. For efficient and safe training, virtual surgery simulation systems have been developed recently. In this paper, we describe the development of a laparoscopic surgery training system using Simulation Open Framework Architecture (SOFA). The simulation software was integrated with a two-hand haptic device specially developed for laparoscopic surgical training. As an example, we focused on the simulation of gallbladder removal surgery using laparoscopic instruments. Gallbladder removal was successfully simulated by the proposed methods. We expect this training system to be similarly successful in simulating a number of other surgical procedures.